2019
DOI: 10.1074/jbc.ra118.006180
|View full text |Cite
|
Sign up to set email alerts
|

A G86R mutation in the calcium-sensor protein GCAP1 alters regulation of retinal guanylyl cyclase and causes dominant cone-rod degeneration

Abstract: 94 fluorescence, indicative of the GCAP1 transition to its RetGC inhibiting state, was suppressed and shifted to a higher Ca 2؉ range. Conformational changes in G86R GCAP1 detectable by isothermal titration calorimetry (ITC) also became less sensitive to Ca 2؉ , and the dose dependence of the G86R GCAP1-RetGC1 complex inhibition by retinal degeneration 3 (RD3) protein was shifted toward higher than normal concentrations. Our results indicate that the flexibility of the hinge region between EF-hands 2 and 3 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 79 publications
11
55
0
Order By: Relevance
“…Biochemical experiments performed with the GC-GCAP1 reconstituted system in the presence of the G86R mutation showed that the complex forms with higher affinity than the WT and it is unable to decelerate the GC at high Ca 2+ -levels corresponding to the dark-adapted state [26]. This mechanism was found to be in line with the clinical cone-rod dystrophy phenotype of the proband and with the autosomal dominant inheritance pattern proven by the segregation study [26].…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…Biochemical experiments performed with the GC-GCAP1 reconstituted system in the presence of the G86R mutation showed that the complex forms with higher affinity than the WT and it is unable to decelerate the GC at high Ca 2+ -levels corresponding to the dark-adapted state [26]. This mechanism was found to be in line with the clinical cone-rod dystrophy phenotype of the proband and with the autosomal dominant inheritance pattern proven by the segregation study [26].…”
Section: Introductionmentioning
confidence: 58%
“…Mutations in GUCA1A, encoding for GCAP1 result in aberrant GC regulation and in retinal degeneration, a set of progressive diseases involving cones, the macula, and in some cases rods, ultimately leading to blindness [11][12][13]. To date, 20 GCAP1 variants have been associated with retinal dystrophy [14][15][16][17][18][19][20][21][22][23][24][25], with one of the most recently discovered being the G86R mutation, located in the previously mentioned hinge region [26]. Biochemical experiments performed with the GC-GCAP1 reconstituted system in the presence of the G86R mutation showed that the complex forms with higher affinity than the WT and it is unable to decelerate the GC at high Ca 2+ -levels corresponding to the dark-adapted state [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of cyclic GMP (cGMP) is an essential process in photoreceptor cells of the retina, as cGMP is the signaltransducing molecule in the light response 1,2 . Mutations in a number of genes that impair or alter cGMP synthesis in rods and cones have been associated to different forms of blindness [3][4][5][6][7][8][9][10][11][12] . Loss-of-function mutations in the RD3 gene (name from the natural strain of "retinal degeneration 3" mice, rd3 locus mutated) cause Leber's congenital amaurosis 12 (LCA12) 13,14 .…”
Section: Introductionmentioning
confidence: 99%